2018
DOI: 10.1590/s0100-83582018360100078
|View full text |Cite
|
Sign up to set email alerts
|

Response of Three Chloris elata Populations to Herbicides Sprayed in Pre- and Post-Emergence

Abstract: In agricultural areas of Brazil, where there is no establishment of cover crops in the off-season and in fruit orchards, an increase in Chloris elata infestations, syn. Chloris polydactyla, has been observed. With the purpose to evaluate the response of three populations (Itaberaí - GO, Matão - SP e Jaboticabal - SP) of C. elata to herbicides sprayed before and after emergence, four experiments were conducted. In the first one, the differential tolerance of three C. elata populations to the herbicide glyphosat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
2
0
1
Order By: Relevance
“…The least control (41 to 51%) was observed with imazamox and nicosulfuron. These results were consistent with Correia and Resende (2018), who previously reported only 27-66% control of C. elata with nicosulfuron. Similarly, Ferguson et al (2019) reported only 53% control of Chloris spp.…”
Section: Percentage Visual Control Of Tumble Windmill Grasssupporting
confidence: 93%
See 2 more Smart Citations
“…The least control (41 to 51%) was observed with imazamox and nicosulfuron. These results were consistent with Correia and Resende (2018), who previously reported only 27-66% control of C. elata with nicosulfuron. Similarly, Ferguson et al (2019) reported only 53% control of Chloris spp.…”
Section: Percentage Visual Control Of Tumble Windmill Grasssupporting
confidence: 93%
“…The least shoot dry biomass reduction of tumble windmill grass was observed with imazamox (43%). These findings are consistent with Correia and Resende (2018), who previously reported > 95% shoot biomass reduction of C. elata at 45 DAT with clethodim, quizalofop, and glyphosate applied at 2-3 tillers stage. In that same study, 47 to 73% shoot biomass reduction of C. elata was observed with nicosulfuron (Correia & Resende, 2018).…”
Section: Percentage Visual Control Of Tumble Windmill Grasssupporting
confidence: 93%
See 1 more Smart Citation
“…Entretanto, no Brasil embora tenha sido introduzida como planta forrageira, pesquisas evidenciaram o alto potencial de infestação e dano econômico da espécie em cultivos anuais de grão, com propagação via sementes (30.000 planta -1 ) e rizomas (CARVALHO et al, 2005), sendo considerada uma planta daninha atualmente, com redução de até 80% sobre a produtividade de grãos na cultura da soja (RASOOL et al, 2017). Recentemente, casos de resistência à molécula herbicida glifosato, inibidor da enzima enolpyruvylshikimato-3 fosfato (EPSPs) foram evidenciados, com dificuldade de controle em áreas infestadas (BRUNHARO et al, 2016;CORREIA;RESENDE, 2018).…”
Section: Introductionunclassified
“…Other species of this genus, such as C. barbata (7), C. virgata (20), C. truncata (19), and C. distichophylla (30) are also reported as resistant. In the last years, these species have gained importance in different crops, mainly grains and sugarcane, thus increasing the number of studies on their biology and management (2,3,9,12,13,25). In addition, no specific recommendations of glyphosate as chemical control of C. elata are available (4).…”
Section: Introductionmentioning
confidence: 99%